2017
DOI: 10.1021/acs.langmuir.7b00097
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Au/Ag Core–Shell Superstructures with Tunable Surface Plasmon Resonance in the Near-Infrared Region and High Performance Surface-Enhanced Raman Scattering

Abstract: Due to the larger surface area and the synergistic effects between two noble metals, the bimetallic superstructures exhibit enhanced distinctive optical, catalytic, and photothermal performances and surface-enhanced Raman scattering (SERS) "hot-spot" effect, and thus have attracted great interest in various applications. Compared with the common Pd, Pt hierarchical structures coated onto Au nanoparticles (NPs), easily synthesized via fast autocatalytic surface growth arising from intrinsic properties of Pd and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 53 publications
5
79
1
Order By: Relevance
“…Following the method developed by Hu, core-shell Au@Pd nanoparticles with tunable sizes were prepared for use in practical SERS-based applications due to their high SERS activity, stability, and reversibility. In addition to synthesizing core-shell structures, a novel route for the Bimetallic AuPd and AuPt nanoparticles have also been extensively studied in terms of their preparation, stabilization, and catalytic activity [50,85,136,137]. Hu et al developed an Au-seeding method by which bimetallic core-shell nanoparticles can be readily synthesized with controllable sizes [88].…”
Section: Seed-mediated Growthmentioning
confidence: 99%
“…Following the method developed by Hu, core-shell Au@Pd nanoparticles with tunable sizes were prepared for use in practical SERS-based applications due to their high SERS activity, stability, and reversibility. In addition to synthesizing core-shell structures, a novel route for the Bimetallic AuPd and AuPt nanoparticles have also been extensively studied in terms of their preparation, stabilization, and catalytic activity [50,85,136,137]. Hu et al developed an Au-seeding method by which bimetallic core-shell nanoparticles can be readily synthesized with controllable sizes [88].…”
Section: Seed-mediated Growthmentioning
confidence: 99%
“…Copyright 2017, Royal Society of Chemistry. c) Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Nanomaterials For Sensingmentioning
confidence: 99%
“…It is reported that the microstructure of the shell material can also influence the SERS enhancement of the adsorbed chemical molecules for Ag‐encapsulated Au nanorods, where it was found that “rough shell” encapsulated Au nanorods showed a higher calculated enhancement value on adsorption of rhodamine (1.97 × 10 8 ) than found for Au nanorods with a “smooth shell” (5.12 × 10 7 ) or for monometallic Au nanorods (4.02 × 10 6 ) . The TEM and STEM images of the bimetallic Au/Ag core–shell superstructures (Figure c,f) and the corresponding high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) elemental mapping data are shown in (Figure d,e).…”
Section: Nanomaterials For Sensingmentioning
confidence: 99%
“…For example, strong reducing agents can create new nuclei in solution, which can lead to the formation of metal nanoparticles having two different sizes [77,78]. Bimetallic Au-Pd and Au-Pt nanoparticles have also been extensively studied in terms of their preparation, stabilization, and catalytic activity [82][83][84][85]. Hu et al developed an Au-seeding method by which bimetallic core-shell nanoparticles can be readily synthesized with controllable sizes [86].…”
Section: Seed-mediated Growthmentioning
confidence: 99%